(untitled) (REMUNOM, 2025)
This study aims to investigate the feeding complaints of atypical children followed at a child CAPS (Psychosocial Care Center). It is a quantitative research with a semi-structured questionnaire containing 20 objective questions. The study sample consists of 10 patients from the child CAPS in the municipality of Patos, Paraíba. The results indicated that the ages of 3-5 and 6-9 were prevalent (30%). Regarding gender, males comprised 100% of the sample, with a prevalence of ADHD diagnoses (50%). 80% are receiving nutritional monitoring, and 60% of the participants had access to food resources. In terms of accepted food quantities, there was a predominance of 4 to 7 foods (70%), and 80% showed a greater preference for industrialized foods. 90% consumed the same foods daily. It was observed that 70% did not show tantrums, 70% had autonomy to feed themselves, and 40% showed food rejection due to the smell and texture of foods. Additionally, 80% did not experience nausea, 60% did not show sensitivity to sounds and lights, and 60% did not experience difficulties eating outside of home. Moreover, 70% did not raise concerns about food at home, and 60% did not have individualized concerns regarding food. Regarding weight, 50% of the mothers considered their children overweight, 50% showed ideal weight for height, and 80% did not use supplements. The study concludes that food selectivity in children with TEA and ADHD is highlighted, with a preference for industrialized foods and predominant carbohydrate intake. The research emphasizes the importance of nutritional monitoring to improve health, reduce social and family impacts, and alleviate sensory symptoms. More studies are needed to expand the findings on this population.Keywords: Food selectivity, ASD, ADHD, nutritional monitoring